PERAN MEDIASI DALAM PENYELESAIAN SENGKETA TANAH ADAT SETRA KARANG RUPIT DI PENGADILAN NEGERI SINGARAJA KELAS 1B - Kadek Oldy Rosy; Dewa Gede Sudika Mangku; Ni Putu Rai Yuliartini (Ganesha Law Review, 2021)
This research aims to know (1) the application of mediation in dispute resolution of Setra Karang Rupit Land at Singaraja Judiciary’s country class 1B (2) to find out the obstacles procedure of mediation dispute custom land in judiciary country class 1B. This research is using an empirical method. Sampling techniques using purposive sampling. The subject of this study was the chairman of the Judiciary’s country of Singaraja class 1B, Bendesa Adat Temukus village, and the object of the study is the role of mediation in dispute resolution of Setra Karang Rupit custom land. The techniques used in this study are document study techniques in Singaraja Judiciary’s country class 1B, interview techniques and observation techniques. The collected Data is analyzed in a qualitative description. The results of the study indicates . (1) In the application of mediation concerning on the dispute resolution Setra Karang Rupit custom land where the evidence of the plaintiff using certificates, testament and parent’s heritage, (2) concern on how about the obstacles in the implementation of the mediation in dispute resolution of Setra Karang Rupit custom land in Singaraja Judiciary’s country class 1B is the plaintiff itself didn’t attending the trial, the legal authority of the plaintiff are resigned during the trial, and the process of the trial itself the plaintiff is too long delayed the way of the trial, so that there’s any obstacles happened.